2018
DOI: 10.1073/pnas.1713930115
|View full text |Cite
|
Sign up to set email alerts
|

Capicua controls Toll/IL-1 signaling targets independently of RTK regulation

Abstract: The HMG-box protein Capicua (Cic) is a conserved transcriptional repressor that functions downstream of receptor tyrosine kinase (RTK) signaling pathways in a relatively simple switch: In the absence of signaling, Cic represses RTK-responsive genes by binding to nearly invariant sites in DNA, whereas activation of RTK signaling down-regulates Cic activity, leading to derepression of its targets. This mechanism controls gene expression in both and mammals, but whether Cic can also function via other regulatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 46 publications
2
48
0
Order By: Relevance
“…During Drosophila development, TLR signaling is initiated when snake cleaves easter, which in turn cleaves spatzle, which then binds to and activates Toll-1 (36). Interestingly, capicua has recently been shown to regulate Toll-1 signaling gene targets (52). Therefore, variations in snake, easter, TLR, and capicua proteins between EGM and AGM populations may alter a TLRcentric signaling pathway that controls wing size.…”
Section: Resultsmentioning
confidence: 99%
“…During Drosophila development, TLR signaling is initiated when snake cleaves easter, which in turn cleaves spatzle, which then binds to and activates Toll-1 (36). Interestingly, capicua has recently been shown to regulate Toll-1 signaling gene targets (52). Therefore, variations in snake, easter, TLR, and capicua proteins between EGM and AGM populations may alter a TLRcentric signaling pathway that controls wing size.…”
Section: Resultsmentioning
confidence: 99%
“…However, our results suggest that in vivo, TF binding to a motif instance is by itself a highly cooperative process that depends on neighboring motifs and syntax. Indeed, in a given cis-regulatory context, lowaffinity motif instances can be an important element of the cis-regulatory code 10,52,117 . The fact that BPNet discovered subtle predictive patterns that are not necessarily strong matches to PWM motif models (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…studies also indicated CIC influences Toll/Interleukin-1 signalling. 17 The most well-known CIC downstream target genes include polyomavirus enhancer activator 3 family members genes, ETV1, ETV4 and ETV5 as well as matrix metalloproteinase 9 (MMP9) 18 and MMP24. 19 In the absence of EGFR-ERK signalling, CIC binds to and represses those genes, while activation of the pathway results in inactivation of CIC through phosphorylation induced degradation or relocalisation from the nucleus to the cytoplasm.…”
Section: Neurogeneticsmentioning
confidence: 99%